Acoustic variability among male gladiator frogs, Boana goiana (Lutz, 1968) (Anura: Hylidae): an 18-year analysis across several reproductive seasons - Andreani, Taina L.; Bastos, Rogerio P.; Dias, Tailise M.; Prado, Cynthia P. A. [UNESP]; Morais, Alessandro R. (Brill, 2021)
Male anurans emit different call types in specific social contexts. Such calls represent a communication pathway for species recognition, mate choice, and male-male competition mediation. The acoustic parameters of these calls can be under directional and/or stabilizing selection due to female choice, which influences intra- and inter-individual call variation. Herein, we investigated the inter-year variation of the advertisement and aggressive calls of the gladiator frog Boana goiana, analysing a temporal series encompassing 18 years of sampling (1996-2014). We measured and analysed the following acoustic parameters: call duration, call repetition rate, number of pulses. pulse duration, pulse repetition rate, and dominant frequency. For both call types. the dominant frequency was classified as a static parameter (CVintra < 5%), while call duration was a dynamic parameter (CVintra > 12%). The advertisement call of B. goiana presents the attributes that could allow individual recognition in the chorus, and we suggest that the aggressive calls might also be important for the individual recognition process. Pulse duration of the advertisement and aggressive calls decreased over the years, as well as the repetition rate of the aggressive calls, which could be related to male body size decrease over the years probably related to habitat alteration. This study provides data on the variation of anuran acoustic features over the longest time span ever analysed. Such studies are less invasive and useful for conservation purposes, since they can detect changes in the reproductive behaviour of populations that might be under environmental modification pressure.
Keywords: advertisement call; aggressive call; Amphibia; calling behaviour; Cerrado biome; individual recognition